Rapid contrast gain reduction following motion adaptation - Nordström, K.; Moyer de Miguel, I.; O'Carroll, D. C. (The Journal of Experimental Biology, 2011)
Neural and sensory systems adapt to prolonged stimulation to allow signaling across broader input ranges than otherwise possible with the limited bandwidth of single neurons and receptors. In the visual system, adaptation takes place at every stage of processing, from the photoreceptors that adapt to prevailing luminance conditions, to higher-order motion-sensitive neurons that adapt to prolonged exposure to motion. Recent experiments using dynamic, fluctuating visual stimuli indicate that adaptation operates on a time scale similar to that of the response itself. Further work from our own laboratory has highlighted the role for rapid motion adaptation in reliable encoding of natural image motion. Physiologically, motion adaptation can be broken down into four separate components. It is not clear from the previous studies which of these motion adaptation components are involved in the fast and dynamic response changes. To investigate the adapted response in more detail, we therefore analyzed the effect of motion adaptation using a test-adapt-test protocol with adapting durations ranging from 20 ms to 20 s. Our results underscore the very rapid rate of motion adaptation, suggesting that under free flight, visual motion-sensitive neurons continuously adapt to the changing scenery. This might help explain recent observations of strong invariance in the response to natural scenes with highly variable contrast and image structure.